Connecting care competencies and culture during disasters - Chhabra, Vivek (Medknow Publications, 2009)
Connecting care Competencies and Culture are core fundamentals in responding to disasters. Thick coordination between professionals, communities and agencies in different geographical areas is crucial to the happening of appropriate preparedness and thus efficient response and mitigation of a disaster. In the next few articles, we present diverse examples related to the preparedness and recovery process to adverse disasters across the globe